IDENTIFICATION OF LAND USE CONFLICTS AND MULTI-SCENARIO ZONING OPTIMIZATION IN THE NORTH BANDUNG AREA - Putut Afandi, Yoga
The history of planning reveals that land is something complex and dynamic, comprised of instruments, procedures, and material outcomes that are constantly changing. Land use conflicts embody the manifestation of uncoordinated development between human systems and their environment. Land use conflicts in the North Bandung Area (NBA) are a significant issue that affects environmental sustainability. This research identifies land use conflicts in the NBA from 2013 to 2018 using sentiment analysis of Twitter data to identify potential conflict locations, involved actors, and spatial metrics as measures of land use conflict characterization in a spatial context. Optimization of zoning in Zone L-1 and L-2 focuses on the balance between development and ecosystem preservation where conflicts are very high. The media highlights these conflicts. Optimization guidance includes a maximum building coverage (KDB) of 10% and a minimum green open space (RTH) of 90%. Optimization in Zones B-1 and B-3 focuses on forestry, ecotourism, and settlements. With development pressures from businesses and communities, priority is given to ecological protection. Land conflicts are at a moderate level with KDB guidance of 30% and RTH of 70%. Zones B-2 and B-4 entail balanced urban development alongside ecological preservation. Despite development support, limitations are imposed with KDB of 30% and RTH of 70%. With a focus on development and zoning limitations, Zone B-5 experiences conflicts between intensive development and ecology. Guidance includes a KDB of 20%, RTH of 80%. This study introduces an integrated conceptual framework for land use conflicts within the planning paradigm, bridging planning methodologies with knowledge systems. It offers an innovative approach by utilizing sentiment analysis and spatial metrics to identify and address land use conflicts. This research can contribute to scientific knowledge in the field.